Bisphenol F induces nonalcoholic fatty liver disease-like changes: Involvement of lysosome disorder in lipid droplet deposition. (15th February 2021) - Wang, Jun; Yu, Pengfei; Xie, Xuexue; Wu, Linlin; Zhou, Manfei; Huan, Fei; Jiang, Lei; Gao, Rong
Abstract: Epidemiological studies have demonstrated that the general population's exposure to bisphenol A (BPA) substitutes is ubiquitous. Bisphenol F (BPF), one of the main BPA substitutes, is increasingly replacing BPA in plastics for food and beverage applications. Accumulating evidence suggests that BPA exposure is associated with nonalcoholic fatty liver disease (NAFLD)-like changes. However, the potential effects of BPF on lipid homeostasis remain poorly understood. In the present study, an epidemiological analysis with LC-MS-MS revealed that the BPF concentrations in the serum of NAFLD patients were significantly higher than those in a control group. Supporting this result, using Oil Red O, BODIPY 493/503, LipidTox Deep Red staining and gas chromatography-time-of-flight mass spectrometry (TOF-MS) assays, we found that BPF exposure induced NAFLD-like changes, with obvious lipid droplet deposition, triglyceride (TG) and fatty acids increase in mouse livers. Meanwhile, lipid droplet deposition and TG increase induced by BPF were also observed in HepG2 cells, accompanied by autophagic flux blockade, including autophagosome accumulation and the decreased degradation of SQSTM1/p62. Using adenoviruses dual-reporter plasmid RFP-GFP-LC3, RFP-GFP-PLIN2 transfection, AO staining, and EGFR degradation assays, we demonstrated that BPF treatment impaired lysosomal degradative capacity, since BPF treatment obviously impaired lysosomal acidification, manifested as decreased lysosomal hydrolase cathepsin L (CTSL) and mature cathepsin D (CTSD) in HepG2 and mouse liver issues. Additionally, v-ATPase D, a multi-subunit enzyme that mediates acidification of eukaryotic intracellular organelles, significantly decreased after BPF exposure in both the vitro and in vivo studies. This study ascertained a novel mechanism involving dysfunctional of lysosomal degradative capacity induced by BPF, which contributes to lipophagic disorders and causes lipid droplet deposition. This work provides evidence that lysosomes may be a target organelle where BPF exerts its potential toxicity; therefore, novel intervention strategies targeting lysosome are promising for BPF-induced NAFLD-like changes. Graphical abstract: Image 1 Highlights: BPF level in serum was higher in NAFLD patients than that in healthy people. BPF contributes to NAFLD like changes in the in vitro and in vitro study. Lysosomal acidification disruption caused by BPF contributes to NAFLD like changes.